Diagnosis of a rare double heterozygous Hb D Punjab/Hb Q India hemoglobinopathy using Sebia capillary zone electrophoresis - Sushama Parab; Suhas Sakhare; Caesar Sengupta; Arokiaswamy Velumani (Wolters Kluwer Medknow Publications, 2014)
In India, hemoglobinopathies constitute a major genetic disorder and hemoglobin variants such as Hb S, Hb D Punjab, and Hb E are the most common ones. Other variants include Hb Q India, Hb Lepore, Hb J Meerut, Hb D Iran, etc. These variants show heterozygous state along with beta thalassemia. However, compound heterozygosities among these variants are very rare. Ethylenediaminetetraacetic acid whole blood sample received for routine thalassemia screening was subjected to alkaline electrophoresis using automated capillary zone electrophoresis. Suspecting the presence of rare variants, further analysis was carried out using Bio-Rad D10 and Tosoh G8 high-performance liquid chromatography (HPLC) systems. Capillary zone electrophoretograms showed the presence of peaks in zone Hb A, Hb D, a fused peak in Hb A2, and a small peak in Z1 zone. Bio-Rad and Tosoh chromatograms also indicated the presence of four peaks which are identified as Hb A, Hb D Punjab, Hb Q India, and hybrid of Hb D Punjab/Hb Q India. A peak in Hb D zone of capillary was due to co-migration of Hb D Punjab and Hb Q India variants. Small peak in Z1 zone indicated the presence of alpha chain variant Hb Q India. The findings were further confirmed by HPLC results and molecular genetic studies. The present study reports for the 1 st time a rare hemoglobinopathy of double heterozygosity for Hb D Punjab, Hb Q India on Capillarys 2 Flex Piercing analyzer and is forth reported case for this rare hemoglobinopathy.